Deciphering the Role of a SLOG Superfamily Protein YpsA in Gram-Positive Bacteria - Brzozowski, Robert S.; Huber, Mirella; Burroughs, A. Maxwell; Graham, Gianni; Walker, Merryck; Alva, Sameeksha S.; Aravind, L.; Eswara, Prahathees J. (Frontiers in Microbiology, 2019)
Bacteria adapt to different environments by regulating cell division and several conditions that modulate cell division have been documented. Understanding how bacteria transduce environmental signals to control cell division is critical to comprehend the global network of cell division regulation. In this article we describe a role for Bacillus subtilis YpsA, an uncharacterized protein of the SLOG superfamily of nucleotide and ligand-binding proteins, in cell division. We observed that YpsA provides protection against oxidative stress as cells lacking ypsA show increased susceptibility to hydrogen peroxide treatment. We found that increased expression of ypsA leads to filamentation and disruption inof the assembly of FtsZ, the tubulin-like essential protein that marks the sites of cell division, in B. subtilis. We also showed that cell division inhibition by YpsA-mediated filamentation is linked to growth rate. Using site-directed mutagenesis, we targeted several conserved residues and generated YpsA variants that are no longer able to inhibit cell division. Finally, we show that the role of YpsA is possibly conserved in Firmicutes, as overproduction of YpsA in Staphylococcus aureus also impairs cell division. Therefore, we propose ypsA to be renamed as griD for growth rate-dependent inhibitor of division.